Patient with very high cardiovascular risk and pseudoresistant arterial hypertension: a focus on treatment adherence - Yu. A. Lutokhina (Лечащий Врач)
Successful detection and management of arterial hypertension play a key role in the control of cardiovascular risks and, consequently, in reducing the incidence of heart attacks and strokes in the population. In the Russian Federation, arterial hypertension is present in a third of the adult population, but not all patients are aware of their disease and receive appropriate treatment. At the same time, despite the large selection of antihypertensive drugs, the effectiveness of treatment is not high enough, and there is a low adherence of patients to taking the prescribed drugs in general. This case report presents a 63-year-old female patient with a very high cardiovascular risk, a history of prior non- ST-elevated myocardial infarction, atrial fibrillation, diabetes mellitus, obesity, hyperlipidemia, hyperuricemia and poorly controlled arterial hypertension. The patient was referred to the Vinogradov Faculty Therapeutic Clinic for «resistant arterial hypertension», but the results of the examination showed that the arterial hypertension was considered to be pseudo-resistant. The variety of previous antihypertensive therapy she received prior to her admission to our clinic included inappropriately low doses of drugs, and the prescribed regimens were difficult to implement, since they assumed drugs were taken during the daytime. There was an inappropriately frequent change of therapeutic regimens instead of increasing doses within the existing regimen. The prescription of antihypertensive drugs in adequate doses, using fixed combinations and a single morning medication administration, as well as careful explanation to the patient the rules of medication administration allowed to achieve the target blood pressure values and to gain control of other modifiable risk factors. Thus, in case of suspected resistant arterial hypertension, the patient's adherence to treatment should first of all be assessed and appropriate doses of antihypertensive drugs should be prescribed. It is necessary to give preference to fixed combinations and, if possible, to avoid complex schemes with two and, moreover, three doses of drugs during the day, since in the modern rhythm of life, even the most accurate patient risks not coping with such prescriptions.